2003
DOI: 10.1590/s1517-74912003000200015
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the relation between the horizontal condylar angle and the internal derangement of the TMJ - a magnetic resonance imaging study

Abstract: ABSTRACT:This research aimed at assessing the relation between the horizontal condylar angle (HCA) and the internal derangement (ID) of the temporomandibular joint (TMJ), as a result of interference by the TMJ disk, in individuals undergoing magnetic resonance (MR) scans. The sample included a total of 144 TMJs (sagittal and coronal views) of 72 subjects, 15 of whom were male and 57 female, with ages ranging from 15 to 70. The scans were made in a Signa system (GE) model at a magnetic field magnitude of 1.5 T.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
29
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 12 publications
4
29
1
1
Order By: Relevance
“…In our study, the high prevalence of flattening may be explained by the possibility that this bone change represents an adaptive alteration, 18,29 the first change of a progressive disease 22 or degenerative change secondary to internal derangement. 24,30 Flattening is also considered a degenerative alteration resulting from overload on the TMJ and it may be related to the involvement of the masseter and temporal muscles.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…In our study, the high prevalence of flattening may be explained by the possibility that this bone change represents an adaptive alteration, 18,29 the first change of a progressive disease 22 or degenerative change secondary to internal derangement. 24,30 Flattening is also considered a degenerative alteration resulting from overload on the TMJ and it may be related to the involvement of the masseter and temporal muscles.…”
Section: Discussionmentioning
confidence: 64%
“…In our study, with the exception of patients aged 80-89 years, the prevalence of bone changes increased with age, as reported by Foucart et al, 19 who assessed the TMJs of patients with disc displacement without reduction, and in agreement with LeResche, 15 who found that pain in the TMJ region occurs in approximately 10% of the population over the age of 18 years. However, Cruzoé-Rebello et al 18 and Isberg et al 20 did not find an association between increased age and an increase in bone changes; they found that a greater number of individuals aged between 20 and 49 years showed TMJ changes.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Some researchers have found no correlation between increasing age and degenerative bone changes. 11,12 High rates of pain, ordered in intensity from high to low, were recorded for the function of the TMJ at rest, during mastication, yawning, and phonation, and on lateral and posterior palpation (from 84.2% to 23.1%). Pain during mandibular function might be related to the degenerative changes present on the articular surface of the joint, since this is exposed to increased loading during mandibular function, while joint pain during palpation may be the result of pathological changes in the lateral and posterior parts of the condyle.…”
mentioning
confidence: 99%